Strengthening social intelligence in social studies learning in Semarang Middle Schools - Sahara, Sahara; Mustofa, Moh. Solehatul; Prajanti, Sucihatiningsih Dian Wisika (Journal of Educational Social Studies, 2024)
The lack of social intelligence in students is something that needs attention. Many factors cause the lack of social intelligence, including the learning process that does not channel the formation of social intelligence in students. Through the independent curriculum, the government seeks to foster students' social intelligence. The research objective examines students' perceptions of the independent curriculum and strengthening social intelligence through social studies learning through the implementation of the independent curriculum at SMPN 22 Semarang and MTs Arrois Cendekia. Researchers applied descriptive qualitative methods with research locations at SMPN 22 Semarang and MTs Arrois Cendekia Semarang.  The results showed that male and female seventh-grade students at SMP N 22 Semarang perceived that the independent curriculum in learning tended to be monotonous, causing laziness to be active during learning.  VII grade students at MTs Arrois Cendekia perceive the independent curriculum in the learning process to be active, innovative, and creative so that it creates a sense of wanting to communicate and socialize among friends when learning takes place. The conclusion of the study shows that the school context and the learning approach used can influence students' perceptions regarding the implementation of an independent curriculum and the form of strengthening social intelligence can be encouraged through the applied learning approach.